2020
DOI: 10.3390/ijerph17103536
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Dissatisfaction on the Self-Esteem of Brazilian Adolescents: A Cross-Sectional Study

Abstract: Background: The present study investigated the influence of body dissatisfaction (BD) on the self-esteem of Brazilian adolescents. Methods: A cross-sectional study was carried out with 1011 students at public and private schools in the city of Fortaleza, Brazil. The body shape questionnaire and the Rosenberg self-esteem scale were applied. Chi-square test, Student’s t-test, Pearson’s correlation, the odds ratio and binary logistic regression were used. Results: The rate of low self-esteem was 33.8% in the adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
0
4
0
1
Order By: Relevance
“…Consistent with earlier scholarly studies, some found similar results among adolescents [ 32 – 34 , 70 ]. Macêdo Uchôa et al studied 1,011 Brazilian students and concluded that adolescents with BD had 5.79 times lower self-esteem in comparisons to adolescents without BD attending public schools (CI 95% 2.06–16.26) and 2.96 times higher in adolescents attending private schools (CI 95%, 1.79–4.88) [ 33 ]. Furthermore, a longitudinal study that followed 440 children for five years, after controlling for confounders, showed BD is a risk factor for depressive mood and low self-esteem in both girls and boys but in different phases of adolescence [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with earlier scholarly studies, some found similar results among adolescents [ 32 – 34 , 70 ]. Macêdo Uchôa et al studied 1,011 Brazilian students and concluded that adolescents with BD had 5.79 times lower self-esteem in comparisons to adolescents without BD attending public schools (CI 95% 2.06–16.26) and 2.96 times higher in adolescents attending private schools (CI 95%, 1.79–4.88) [ 33 ]. Furthermore, a longitudinal study that followed 440 children for five years, after controlling for confounders, showed BD is a risk factor for depressive mood and low self-esteem in both girls and boys but in different phases of adolescence [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It integrated different factors and their association with BD among a single ethnic group of older adolescents. The majority of studies were done on young adults [ 5 , 16 , 73 , 76 ] while others were done on the entire adolescent period (10–19 years old) [ 5 , 13 ] or early adolescence [ 26 , 81 ], few studies were done on older adolescents [ 25 , 33 , 70 ]. The third contribution was the use of BD subscale of EDI-2, as the majority of studies used the stunkard figure rating scale silhouette [ 10 , 16 , 26 , 73 ] which the arrangement of figure may cause reporting bias toward thinner Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents and young adults internalize physically beautiful body shapes. If internalization is unsuccessful, dissatisfaction with their bodies and the constant search for it may result in risky behaviors, that may lead to the development of eating disorders (62). Even if the development of a mental disorder, such as an eating disorder, does not occur, the strength of the ideal of thinness is significantly positively correlated with depressive tendencies, anxiety, and low self-esteem (63).…”
Section: Personality Characteristics (Tipi-j)mentioning
confidence: 99%
“…La insatisfacción corporal, definida como la percepción negativa sobre la imagen corporal, es cada vez más frecuente en nuestra sociedad, se ha reportado una prevalencia en adolescentes de entre un 30-40%, la cual puede variar según el género y la población estudiada 9 . La insatisfacción corporal cobra importancia en la adolescencia, por su relación con la baja autoestima, la depresión y trastornos de la conducta alimentaria (TCA) 8,10 .…”
Section: Introductionunclassified